Vexy thing on gender and liberation - Perry, Imani 1972- (Duke University Press, 2018)
Seafaring, sovereignty, and the self : of patriarchy and the conditions of modernity -- Producing personhood : the rise of capitalism and the Western subject -- Interlude 1. How did we get here? nobody's supposed to be here -- In the ether : neoliberalism and entrepreneurial woman -- Simulacra child : hypermedia and the mediated subject -- Sticks broken at the river : the security state and the violence of manhood -- Interlude 2. Returning to the witches -- Unmaking the territory and remapping the landscape -- The utterance of my name : invitation and the disorder of desire -- The vicar of liberation
Includes bibliographical references and index. - Description based on print version record
Keywords: Geschichte; Patriarchy; Feminism; Frauenbewegung; Kritik; Patriarchat